Percepciones ambientales sobre contaminación atmosférica de los estudiantes del Instituto Superior Pedagógico Loreto, especialidad educación primaria en Iquitos. Perú. 2020 - Da Silva Perez, Jonehi Josmar (2023)
The research was carried out to identify the knowledge that students of the Higher Pedagogical Institute of Iquitos (ISPL) have regarding air pollution. The research design is non-experimental, qualitative-quantitative. The sample was 60 students enrolled in 2020, specializing in primary education. The results indicate air pollution as a low intensity problem (4.4%) within the city’s problems. Specifically regarding air pollution, they consider it a non-relevant problem for the city (50%), they do not know about the information on air pollution levels in the city (53.2%), they affirm that it is unreliable (13.3%), and this type of information about the problem under study is rarely known (83.4%). Regarding air pollution in Iquitos, respondents report that it is average (86.7%) to low (13.3%); affecting health from fair (83.3%) to poor (11.7%). Iquitos compared to other cities they say that the level of pollution is regular (46.7%). They think they do not feel when the pollution is high or low, they think that this situation is rarely the case (75%). If the problem existed, it would affect the elderly (51.7%) and children (25%). The main complaints would be headaches (66.7%), eye irritation (58.3%), flu (83.3%), stress (83.3%) among other complaints. Regarding the environmental perception of the city of Iquitos and the atmosphere, people consider it (91.7%) clean, also in their districts Punchana 50%, San Juan 86.7% and Belén (76.7%); Regarding air quality in the future, 92% report that it will worsen, due to the increase in factories (83%), vehicle fleet (42%), use of aerosols (67%), dust (87%), burning of waste (83%) and unpleasant odors (55%). To improve the city’s air quality, they recommend recycling garbage (100%), not burning waste (100%), cooperate with government measures (83%), use less chemicals (83%), summarizing everything, do not contaminate (100%).